Performance, Hybridity and Convergence in the Poetry of Alice Oswald and Kae Tempest - Bastien Goursaud (Sillages Critiques)
This paper looks at two poets, Alice Oswald and Kae Tempest, whose works are largely influenced by oral performance and exist on a plurality of media that are made easily accessible by the Internet. It posits that all actualisations of the poem – whether in a poetry book, a recording, a video, or a live performance – are equally important and must be studied in contrast to one another as part of the poetry collection. The latter term is therefore defined as the gathering of all the actualisations of the poem and their relationships. It then examines the poetics of hybridity that such intermedia poems produce and the plural poetic experience they create. It considers the poems in the light of Henry Jenkins’s concept of “convergence culture,” before suggesting that cette convergence is related to the emergence of a poetic community – i.e. a community produced by the oral poem and its plural versions, which is mirrored by the poem itself. Finally, it suggests that such interest in the community may provide a fruitful way of grouping together and comparing works in the diverse field of contemporary British poetry.